Pelanggaran Prinsip Kesantunan dalam Anime Haikyuu!! Season 2 - Kusumah, Irma Putri Kartini; Yuliani Giri, Ni Luh Kade; Pradhana, Ngurah Indra (LANCAH: Jurnal Inovasi dan Tren, 2024)
The study entitled "Violations of Politeness Principles in the Anime Haikyuu!! Season 2" aims to describe the violations of politeness principles, the factors underlying these violations, and the responses to these violations. This research is a pragmatic study using a politeness analysis approach. The theories used are the politeness theories of Leech, Mizutani and Mizutani, and Austin's perlocutionary acts. The research method employed is qualitative. Based on the research findings, it was discovered that: 1) Violations of politeness maxims occurred in the maxims of tact, generosity, approbation, modesty, agreement, and sympathy. The violations were predominantly in the approbation maxim because the speakers aimed to create a casual atmosphere. 2) The factors underlying the violations of politeness maxims include the level of familiarity, age, social status, gender, group membership, and situation. Gender and situation factors predominantly cause violations of politeness maxims, as most speakers are of the same gender and the utterances occur in informal contexts. 3) The perlocutionary acts resulting from the violations of politeness maxims include hindering, encouraging, condemning, convincing, annoying, relieving, embarrassing, frightening, distracting, inspiring, impressing, and boring. Among these twelve perlocutionary acts, convincing was the most frequently found because the majority of the violations by the speakers aimed to persuade the interlocutors of their opinions and feelings of annoyance from the interlocutor.